1988
DOI: 10.1001/archderm.1988.01670090020004
|View full text |Cite
|
Sign up to set email alerts
|

The Cutaneous Immunopathology of Necrobiosis Lipoidica Diabeticorum

Abstract: Twelve female patients with necrobiosis lipoidica diabeticorum (six with diabetes and six without) had a 5-mm punch biopsy of the skin lesion performed. The tissue was processed for dermatopathologic examination in 12 cases and for direct immunofluorescence in 11. Vasculopathy with inflammation and thickening of vessel walls, at times leading to occlusion, was found in lesional skin in all 12 cases. Vessels contained deposits of immunoreactants in the involved skin in 11 cases. This included IgM in six, C3 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…The legs are most commonly affected. It has been reported that NLD resolves with good control of diabetes [1,2]. Here we report an unusual case in which NLD developed in the periorbital region.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…The legs are most commonly affected. It has been reported that NLD resolves with good control of diabetes [1,2]. Here we report an unusual case in which NLD developed in the periorbital region.…”
Section: Introductionmentioning
confidence: 74%
“…The legs are most frequently affected, but NLD can also involve the hands, fingers, and forearms [1,2]. Scalp involvement has been reported in a few cases [3,4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many theories have been proposed, including a diabetic microangiopathy (9), basement membrane thickening (10), immune complex disease (11) and abnormalities of collagen synthesis and degradation (12). The findings of immunoreactants IgM, IgG, IgA, and C3 deposited in blood vessel walls of both lesional and uninvolved skin of individuals with NL and of vasculitis support the role of immunologically mediated vascular disease as the primary cause of altered collagen in NL (11). Microangiopathic vascular changes seen in individuals with diabetes mellitus and increased platelet aggregation have also been implicated.…”
Section: Discussionmentioning
confidence: 97%
“…4 These characteristics were more prominent in diabetic patients than nondiabetics. 9 In a study of 10 idiopathic cases of NL, investigators found that oxygen tension was lower but laser Doppler fluxes were increased around NL lesions in response to hyperemic stimuli. 10 The alterations seen in NL lesions were thought to be caused by glycoprotein deposition, which can be responsible for thickening and occlusion of blood vessels.…”
Section: Blood Vesselsmentioning
confidence: 99%